Adverse 30-Day Clinical Outcomes and Long-Term Mortality Among Patients With Preprocedural Atrial Fibrillation Undergoing Percutaneous Coronary Intervention - Batchelor, R.J.; Dinh, D.; Noaman, S.; Brennan, A.; Clark, D.; Ajani, A.; Freeman, M.; Stub, D.; Reid, Christopher; Oqueli, E.; Yip, T.; Shaw, J.; et al. (ELSEVIER SCIENCE INC, 2022)
Objectives: Approximately 5–10% of patients presenting for percutaneous coronary intervention (PCI) have concurrent atrial fibrillation (AF). To what extent AF portends adverse long-term outcomes in these patients remains to be defined. Methods: We analysed data from the multicentre Melbourne Interventional Group Registry from 2014–2018. Patients were identified as being in AF or sinus rhythm (SR) at the commencement of PCI. The primary endpoint was long-term mortality, obtained via linkage with the National Death Index. Results: 13,286 procedures were included, with 800 (6.0%) patients in AF and 12,486 (94.0%) in SR. Compared to SR, patients with AF were older (72.9±10.9 vs 64.1±12.0 p<0.001) and more likely to have comorbidities including diabetes mellitus (31.3% vs 25.0% p<0.001), hypertension (74.4% vs 65.1% p<0.001) and moderate to severe left ventricular systolic dysfunction (36.6% vs 19.5% p<0.001). Atrial fibrillation was associated with an increased risk of in-hospital mortality (11.0% vs 2.5% p<0.001) and MACE (composite of all-cause mortality, myocardial infarction, or target vessel revascularisation) (11.9% vs 4.2% p<0.001). In-hospital major bleeding was more common in the AF group (3.1% vs 1.0% p<0.001). On Cox proportional hazards modelling, AF was an independent predictor of long-term mortality (adjusted HR 1.38 95% CI 1.11–1.72 p<0.004) at a mean follow-up of 2.3±1.5 years. Conclusions: Preprocedural AF is common among patients presenting for PCI. Preprocedural AF is associated with high-rates of comorbid illnesses and portends higher risk of short- and long-term outcomes including mortality underscoring the need for careful evaluation of its risks prior to PCI.